Obesity, Male Reproductive Function and Bariatric Surgery - Di Vincenzo, Angelo; Busetto, Luca; Vettor, Roberto; Rossato, Marco (Frontiers in Endocrinology, 2018)
Overweight and obesity are associated with several chronic complications, such as type 2 diabetes, arterial hypertension and atherosclerotic cardiovascular diseases, with relevant consequences for patients and public health systems. Reproductive function abnormalities, such as obesity-related secondary hypogonadism, erectile dysfunction and infertility, represent other abnormalities negatively affecting the quality of life of men suffering from obesity but, despite their high prevalence, these are often understated because of a general lack of awareness in clinical practice. Obesity and gonadal function are closely related, with obesity being associated with hypogonadism that is reversed by body weight reduction thus ameliorating reproductive and sexual health. Clinical studies specifically evaluating the impact of non-surgical weight loss on testosterone levels sometimes showed conflicting results, whereas extensive literature has demonstrated that weight loss after bariatric surgery is correlated with an increase in testosterone levels greater than that obtained with only lifestyle interventions, suggesting the role of surgery also for the treatment of hypogonadism in obese male. However, studies concerning the consequences of bariatric surgery on overall reproductive function in the male, including also sexual activity and fertility, are limited and data regarding long-term effects are lacking. Here we present a brief review summarizing the evidence regarding the interplay between obesity and reproductive abnormalities in the obese male, together with the role of bariatric surgery for the treatment of these complications, describing both the positive effects and the limitations of this procedure.